Impact of the COVID-19 Pandemic on the Welfare of Animals in Australia - Baptista, Jacqueline; Blache, Dominique; Cox-Witton, Keren; Craddock, Nicola; Dalziel, Toni; de Graaff, Nicolas; Fernandes, Jill; Green, Ronda; Jenkins, Helen; Kahn, Sarah; Kelly, Deborah; Lauber, Mariko; et al. (Frontiers in Veterinary Science, 2021)
We report on the various responses in Australia during 2020 to minimize negative impacts of the COVID-19 pandemic on the welfare of animals. Most organizations and individuals with animals under their care had emergency preparedness plans in place for various scenarios; however, the restrictions on human movement to contain the spread of COVID-19, coupled with the economic impact and the health effects of COVID-19 on the skilled workforce, constituted a new threat to animal welfare for which there was no blueprint. The spontaneous formation of a national, multisectoral response group on animal welfare, consisting of more than 34 organizations with animals under their care, facilitated information flow during the crisis, which helped to mitigate some of the shocks to different organizations and to ensure continuity of care for animals during the pandemic. We conclude that animal welfare is a shared responsibility, and accordingly, a multisectoral approach to animal welfare during a crisis is required. Our experience demonstrates that to safeguard animal welfare during crises, nations should consider the following: a national risk assessment, clear communication channels, contingency plans for animal welfare, a crisis response group, and support systems for animal care providers. Our findings and recommendations from the Australian context may inform other countries to ensure that animal welfare is not compromised during the course of unpredictable events.